2021
DOI: 10.1021/jacs.1c04432
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Site Inhibitor of CBP/p300 KIX is a Selective and Effective Modulator of Myb

Abstract: The protein–protein interaction between the KIX motif of the transcriptional coactivator CBP/p300 and the transcriptional activator Myb is a high-value target due to its established role in certain acute myeloid leukemias (AML) and potential contributions to other cancers. However, the CBP/p300 KIX domain has multiple binding sites, several structural homologues, many binding partners, and substantial conformational plasticity, making it challenging to specifically target using small-molecule inhibitors. Here,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…No binding was observed for the M/M-5A peptide. These values are in good agreement with a recent report for a similar peptide fusion of MYB and MLL, which reported K d values in the low nanomolar range for the CREBBP/ EP300 KIX domain (31).…”
Section: An Alanine-versus-aspartate Difference In the Ep300 And Creb...supporting
confidence: 93%
“…No binding was observed for the M/M-5A peptide. These values are in good agreement with a recent report for a similar peptide fusion of MYB and MLL, which reported K d values in the low nanomolar range for the CREBBP/ EP300 KIX domain (31).…”
Section: An Alanine-versus-aspartate Difference In the Ep300 And Creb...supporting
confidence: 93%
“…The conformational plasticity of KIX and a lack of contiguous binding pockets on its surface have made the discovery of potent ligands difficultmany small molecules and peptides designed or isolated from the above strategies have shown weak affinity in the high micromolar to millimolar range for KIX. A potent peptide ligand that links cMyb and MLL sequences was recently described; this study further illustrates the challenge in targeting an individual KIX cavity with low to medium molecular weight compounds …”
Section: Introductionmentioning
confidence: 64%
“…A potent peptide ligand that links cMyb and MLL sequences was recently described; this study further illustrates the challenge in targeting an individual KIX cavity with low to medium molecular weight compounds. 17 In our previous studies, we used the computational algorithm AlphaSpace 18 to topographically map protein surfaces and design natural and nonnatural side chains on peptide mimics. AlphaSpace analysis suggested that several MLL residues do not optimally occupy the closest lying pockets on KIX (Figure 1B) and that nonnatural residues may be designed to capture cryptic pockets.…”
Section: ■ Introductionmentioning
confidence: 99%
“…CBP/p300 KIX inhibitor MybLL (Figure 2), which links the TADs of Myb, and MLL to form a sub-nM dual-site inhibitor of KIX (Joy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Such large peptides are oftentimes difficult to advance to clinical studies due to several challenging pharmacokinetic and pharmacodynamic (PK/PD) properties, such as low stability and poor tissue distribution (Diao and Meibohm, 2013). Additionally, the most potent and selective peptide inhibitors are based on the relatively well-structured regions of the TAD when it is bound to the coactivator (Ramaswamy et al, 2018;Joy et al, 2021). Fuzzy TF interactions that have more limited structural formation are therefore not likely to benefit from this approach.…”
Section: Introductionmentioning
confidence: 99%